Continuidades e mudanças na promoção dos interesses nacionais americanos no pós-guerra fria - Contrera, Flávio (2013)
For over forty years the struggle against the spread of communism dominated the U.S. foreign policy agenda. However the end of the Cold War proved the limits of the containment strategy front the emergence of new and complex challenges. Without a vital security threat, the U.S. had great difficulty to define and promote their national interests. The Post-Cold War era has been marked by a dominance of smaller-scale threats, often transnational in scope, and was characterized, from the beginning, by lack of clarity of Americans with respect to their international objectives. At the end of the 1990s, some authors stated that the U.S. government would have given more emphasis in this context to the promotion of economic, ethnic and humanitarian interests, rather than potentially more vital threats to the survival of the country. These works, however, not delimited the concept of national interest and not identified this from the analysis of an official policy document. Keeping this in mind, we start from the perception that national interests are policies defined by policymakers together with the President to pursue certain goals abroad. As such, those composing, as required by law, the U.S. National Security Strategy. Thus, by analyzing the annual editions of this document, published between 1987 and 2000, the main objective of our work consisted to evaluate whether in the absence of a vital threat to U.S. security in the post-Cold War, it would have taken a redefinition of American national interest s agenda. In short, data showed that during the Clinton administration security interests had reduced their emphasis. The absence of a vital threat and the predominance of secondary threats resulted in a national interest s agenda more focused on "economic well-being and promotion of values" and less oriented to "defense of the nation and favorable world order". This decline of security as a priority issue was also accompanied by a trend of decreasing in U.S. military spending and also a substantial increase in spending on U.S. foreign economic assistance programs, which suggests, in fact, a redefinition of the country's priorities in the Post-Cold War context.